Environmental hazards and disasters : contexts, perspectives and management - Paul, Bimal Kanti (Chichester : Wiley-Blackwell, 2011)
Environmental Hazards and Disasters: Contexts, Perspectives and Management focuses on manifested threats to humans and their welfare as a result of natural disasters. The book uses an integrative approach to address socio-cultural, political and physical components of the disaster process. Human and social vulnerability as well as risk to environmental hazards are explored within the comprehensive context of diverse natural hazards and disasters. In addition to scientific explanations of disastrous occurrences, people and governments of hazard-prone countries often have their own interpretation.
Includes bibliographical references and index.
Print version record.
Keywords: Hazardous geographic environments; Disasters; Natural disasters; Human ecology; NATURE -- Natural Disasters; SOCIAL SCIENCE -- Disasters & Disaster Relief; Disasters; Hazardous geographic environments; Human ecology; Natural disasters; Naturkatastrophe; Risiko; Electronic books